Species Diversity and Potential Use of Asteraceae in Tawangmangu, Karanganyar Regency, Central Java - Mutiara Fauziana; Ratna Susandarini (Journal of Tropical Biodiversity and Biotechnology, 2019)
Asteraceae is a group of plants with high species diversity, with about 25.000 species become members of this family worldwide. This family has many potential uses such as medicinal plants, ornamental plants and weeds. Tawangmangu is an area with unspoiled environmental conditions, where Asteraceae plants are found either wildly or deliberately cultivated in this area. This study aims to determine species diversity of Asteraceae and their potential use. This study was conducted in 5 villages namely Plumbon, Nglebak, Karanglo, Tawangmangu and Kalisoro. The samples were collected with random sampling method, while information on potential use of Asteraceae was gathered from literature studies and interviews with local people. Results of this study are expected to be basic data of species diversity as well as to provide reference of their potential use. A total of 32 species were found on various habitat, include roadside, home yard, riparian of river, in irrigation canal, and on agricultural landscape. The specimens found were all have potential as medicinal plants, with some wild plants were commonly known as weeds, many others were having potential as ornamental plants.